1997
DOI: 10.1037/0097-7403.23.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Configural analysis of summation in autoshaping.

Abstract: In 4 experiments, pigeons received autosbaping with various combinations of three stimuli, A, B, and C, before test trials in which responding during all three stimuli, ABC, was compared with that during a three-element control compound, DEF, which had been consistently paired with food. Pairing A, B, and C individually with food resulted in similar rates of responding during ABC and DEF (Experiments 1 and 2). Responding was faster, however, during ABC than during DEF after training in which food was signaled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 35 publications
5
64
2
Order By: Relevance
“…This provides a ready explanation for the failures to observe summation between two auditory CSs in rabbit nictitating-membrane conditioning and between two visual stimuli in autoshaping with pigeons. It also provides an explanation for conflicting data reported by Pearce, Aydin, and Redhead (1997) and Myers, Vogel, Shin, & Wagner (2001). Both groups conducted an experiment that compared responding to a triple compound, ABC, between animals trained with each CS individually (A+ B+ C+) and animals trained with the same CSs as three pairwise compounds (AB+ AC+ BC+).…”
Section: The Replaced Elements Theorymentioning
confidence: 99%
“…This provides a ready explanation for the failures to observe summation between two auditory CSs in rabbit nictitating-membrane conditioning and between two visual stimuli in autoshaping with pigeons. It also provides an explanation for conflicting data reported by Pearce, Aydin, and Redhead (1997) and Myers, Vogel, Shin, & Wagner (2001). Both groups conducted an experiment that compared responding to a triple compound, ABC, between animals trained with each CS individually (A+ B+ C+) and animals trained with the same CSs as three pairwise compounds (AB+ AC+ BC+).…”
Section: The Replaced Elements Theorymentioning
confidence: 99%
“…Stimulus control has also been and still is a central subject in experimental psychology (see e.g. Terrace, 1966;Mackintosh, 1974;Pearce et al, 1997). One of the fundamental observations on how stimuli control response is referred to as stimulus generalization in psychology (Guttman & Kalish, 1956;Mackintosh, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…That is, they found much greater summation to ABC in rabbits trained with the single CSs than in rabbits trained with the two-stimulus compounds. Myers et al argued that the difference between the two experiments was that their stimuli were from different modalities (one visual, one auditory, and one vibrotactile), whereas the stimuli used by Pearce et al (1997) were all visual. Wagner (2003) has shown that the replaced elements model can account for both sets of findings by assuming that the stimuli used by Pearce et al (1997) underwent substantial replacement when compounded, whereas the stimuli used by Myers et al underwent little replacement.…”
Section: Summation Across Compounds After Negative Patterningmentioning
confidence: 99%
“…Pearce, Aydin, and Redhead (1997) compared responding to a triple compound, ABC, between two groups of pigeons in an autoshaping experiment. One group had been trained with each of the CSs individually (A , B , and C ); the other group had been trained with the same three stimuli as three pairwise compounds (AB , AC , and BC ).…”
Section: Summation Across Compounds After Negative Patterningmentioning
confidence: 99%